(untitled) (Journal of Face Aesthetics, 2021)
Introduction. There is an increase in the popularity of aesthetic treatment among increasingly younger groups of people, which also includes medical students. Their decisions are often dictated by their own acquired knowledge in this area of expertise. Aim. To estimate the number and determine the age threshold for the use of cosmetology and facial aesthetic medicine among Polish and English-speaking students. Material and Methods. The statistical analysis included 240 questionnaires (175 females and 65 males) addressed to Polish and English-speaking students in 3rd, 4th, and 5th year studies within the field of dentistry at the Medical University of Poznań in 2019 and 2020. The Pearson chi-squared test was performed to determine the significance of this test (p < 0.05). Results. Most of the respondents (89%) confirm that they use necessary facial aesthetic and cosmetology treatments. Moreover, the number of opposing respondents decreases within the next year of dental education. The respondents indicated that the treatments should be started at the age of 25–30 or 30–35. About 82% of Polish-speaking students and 75% of English-speaking students have not used these types of treatments thus far. Conclusions. The level of acquired medical and dental knowledge influences the tendency of students to undergo facial aesthetic and cosmetic treatments.